2022
DOI: 10.1177/23259582221096522
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Barriers to Viral Suppression among People with HIV in Santiago, Dominican Republic

Abstract: The Dominican Republic (DR) has the second-highest prevalence of HIV infection in the Caribbean, but viral suppression and treatment adherence are not well understood. We conducted a cross-sectional study among people living with HIV/AIDS(PLWHA) to fill in the knowledge gap. Questionnaire was used to collect demographic data, antiretroviral therapy (ART) adherence, and barriers and facilitators to HIV care. Viral load and other clinical information were extracted through chart reviews. Descriptive analyzes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This proportion was consistently similar in all the population demographic strata. This is similar to findings published from other regions, such as Guatemala in Central America ( 18 ) and the Dominican Republic in the Caribbean region ( 19 ). This suggests that such outcomes are attainable in diverse settings.…”
Section: Discussionsupporting
confidence: 90%
“…This proportion was consistently similar in all the population demographic strata. This is similar to findings published from other regions, such as Guatemala in Central America ( 18 ) and the Dominican Republic in the Caribbean region ( 19 ). This suggests that such outcomes are attainable in diverse settings.…”
Section: Discussionsupporting
confidence: 90%
“…This study associated higher levels of stigma with higher odds of missing an ART dose [ 25 ]. A study evaluating barriers to viral suppression among PLHIV in the DR found that male and employed patients were more likely not to be virally suppressed, partially due to stigma that limited engagement in care [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with stigma, low social support has been widely recognized as a factor adversely affecting engagement in HIV care [ 26 ]. In a DR-based study with WLHIV, participants described controlling disclosure, educating self and others about HIV, and seeking support from family, friends, or others [ 27 ].…”
Section: Introductionmentioning
confidence: 99%